From lab to real world: Heat acclimation considerations for elite athletes - Casadio, J. R.; Kilding, A. E.; Cotter, J. D.; Laursen, P. B. (Sports Medicine, 2017)
As major sporting events are often held in hot environments, increased interest in ways of optimally heat acclimating athletes to maximise performance has emerged. Heat acclimation involves repeated exercise sessions in hot conditions that induce physiological and thermoregulatory adaptations that attenuate heat-induced performance impairments. Current evidence-based guidelines for heat acclimation are clear, but the application of these recommendations is not always aligned with the time commitments and training priorities of elite athletes. Alternative forms of heat acclimation investigated include hot water immersion and sauna bathing, yet uncertainty remains around the efficacy of these methods for reducing heat-induced performance impairments, as well as how this form of heat stress may add to an athlete`s overall training load. An understanding of how to optimally prescribe and periodise heat acclimation based on the performance determinants of a given event is limited, as is knowledge of how heat acclimation may affect the quality of concurrent training sessions. Finally, differences in individual athlete responses to heat acclimation need to be considered. This article addresses alternative methods of heat acclimation and heat exposure, explores gaps in literature around understanding the real world application of heat acclimation for athletes, and highlights specific athlete considerations for practitioners.